ANALISIS EFEKTIFITAS KINERJA EXCAVATOR PADA AKTIFITAS OB REMOVAL PENAMBANGAN BATUBARAMENGGUNAKAN METODE OEE (STUDI KASUS: PT. RML EMBALUT – KALIMANTAN TIMUR) - Arif Nuryono (Journal Industrial Manufacturing, 2018)
Performance measurement in manufacturing industry is usually measured with the approach of OEE (Overall Equipment Effectiveness). In the mining industry, backhoe excavator performance can also be measured by OEE value approach. OEE value measurement performed on the excavator in coal mine Embalut Kaltim. In the case study on the company, the performance analysis also compared with the backhoe excavator defined performance targets of the company. OEE Value mine done OEE parameter modification into 3 dimensions: availability, utilization and productivity index. OEE measurement mine OB Removal devoted to the activity, as this activity has a value greater than most activity cost Getting Coal. The measurement results OEE values for the existing conditions is very low. Two of six units which have a low OEE value. The low value of OEE most influential is the utilization value. If compared with OEE value targets, there are five units of backhoe has a value below the target. Efforts are being made to improve OEE values is by the application of TPM: implementing autonomous maintenance, implementation of SMED: change the internal activity into external and doing jobs that could be eliminated or Parallelize and application 5W1H: make your creative ideas by way of brainstorming or explore the idea of problem solving, After implementation of the improvement idea, the value of simulation obtained quite good, an increase compared with OEE value before improvement. Keyword : Availability, Utilization, Productivity Index, TPM, SMED, 5W1H.